2005
DOI: 10.1172/jci200523493
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of IKK2 in hepatocytes does not sensitize these cells to TNF-induced apoptosis but protects from ischemia/reperfusion injury

Abstract: The inhibitor of NF-κB (I-κB) kinase (IKK) complex consists of 3 subunits, IKK1, IKK2, and NF-κB essential modulator (NEMO), and is involved in the activation of NF-κB by various stimuli. IKK2 or NEMO constitutive knockout mice die during embryogenesis as a result of massive hepatic apoptosis. Therefore, we examined the role of IKK2 in TNF-induced apoptosis and ischemia/reperfusion (I/R) injury in the liver by using conditional knockout mice. Hepatocyte-specific ablation of IKK2 did not lead to impaired activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 45 publications
7
65
1
Order By: Relevance
“…Indeed, inhibition of JNK results in a reduction of ConA-induced liver damage, demonstrating that the primary mechanisms by which IKKβ-dependent NF-κB activation prevents TNFα-induced apoptosis in vivo is through attenuation of JNK activation (discussed below) (Maeda et al, 2003; Wullaert et al, 2007). Another study showed that hepatocyte-specific deletion of IKKβ does not lead to increased apoptosis upon challenge with ConA, which is in sharp contrast with previous results (Luedde et al, 2005). Yet, activation of NF-κB signalling after pharmacological inhibition of IKKβ was not impaired after TNFα stimulation.…”
Section: Role Of Nf-κb In Health and Liver Diseasecontrasting
confidence: 96%
See 1 more Smart Citation
“…Indeed, inhibition of JNK results in a reduction of ConA-induced liver damage, demonstrating that the primary mechanisms by which IKKβ-dependent NF-κB activation prevents TNFα-induced apoptosis in vivo is through attenuation of JNK activation (discussed below) (Maeda et al, 2003; Wullaert et al, 2007). Another study showed that hepatocyte-specific deletion of IKKβ does not lead to increased apoptosis upon challenge with ConA, which is in sharp contrast with previous results (Luedde et al, 2005). Yet, activation of NF-κB signalling after pharmacological inhibition of IKKβ was not impaired after TNFα stimulation.…”
Section: Role Of Nf-κb In Health and Liver Diseasecontrasting
confidence: 96%
“…Indeed, some reports shown that administration of LPS in IKKβΔHep mice induces similar degree of liver damage than in the wild-type strain (Maeda et al, 2003). Consistent with these findings, Trautwein and colleagues recently found that injectable TNFα or challenge with LPS does not sensitize livers of either IKKβΔHep or another mouse model IKKβ f/f -Mx-Cre, which after Cre -mediated recombination showed an efficient knockout of IKKβ in Kupffer, non-parenchymal and lymphoid cells (Luedde et al, 2005). A possible explanation for the selective role of IKKβ and NF-κB in liver protection against ConA-induced apoptosis manifests because this agent induces membrane-bound TNFα expression from cells, which can then activates both TNF-R1 and TNF-R2 in hepatocytes.…”
Section: Role Of Nf-κb In Health and Liver Diseasementioning
confidence: 72%
“…Activation of NFkB 8 and subsequent transcription and release of TNFa are crucial events in the evolution of reperfusion injury, 6 4 and are particularly important for inflammation in the post-ischaemic liver. 8 To assess whether the impaired induction of NFkB-binding activity leads to reduced transcription of TNFa, 25 26 we quantified TNFa mRNA levels by real time polymerase chain reaction. After 1 h of ischaemia and 1 h of reperfusion, expression levels of mRNA for TNFa increased about fivefold in control animals.…”
Section: Is Post-ischaemic Activation Of Nfkb Altered In Cholestasis?mentioning
confidence: 99%
“…8 This cascade mediates inflammation in the post-ischaemic liver, leading to additional injury and necrosis, typically peaking 24 h after reperfusion in the mouse model. Cholestatic animals are characterised by an increased release of cytokines, increased inflammation and a higher lethality when injected with lipopolysaccharide (LPS) or the Gramnegative pathogen Escherechia coli.…”
mentioning
confidence: 99%
“…Recent publications tried to shed some light on this issue in vivo 5 6 7 8. Since constitutive NF-κB knock-out mice die during embryogenesis,9 an approach guided by the creation of conditional knock-out animals was pursued.…”
mentioning
confidence: 99%